Hedge fund activism in Japan : the limits of shareholder primacy - Buchanan, John, 1951- (Cambridge University Press, 2012)
"Hedge fund activism is an expression of shareholder primacy, an idea that has come to dominate discussion of corporate governance theory and practice worldwide over the past two decades. This book provides a thorough examination of public and often confrontational hedge fund activism in Japan in the period between 2001 and the full onset of the global financial crisis in 2008. In Japan this shareholder-centric conception of the company espoused by activist hedge funds clashed with the alternative Japanese conception of the company as an enduring organisation or a 'community'. By analysing this clash, the book derives a fresh view of the practices underpinning corporate governance in Japan and offers suggestions regarding the validity of the shareholder primacy ideas currently at the heart of US and UK beliefs about the purpose of the firm"--